Life satisfaction and associated social factors among college students in Kottayam district, Kerala - Thomas, Naveen; Abraham, Joe; Johns, Felix (International Journal Of Community Medicine And Public Health, 2023)
Background: Fostering youth wellbeing is a pressing concern for educators and mental health professionals. It is generally acknowledged that among many constructs, understanding and promoting social support and life satisfaction are essential to achieving this goal. This study was conducted to assess the level of life satisfaction and social support and to determine the relationship of social support and socio-demographic factors with life satisfaction among students of arts and science colleges in Kottayam district. Methods: A cross-sectional study was conducted among 464 undergraduate students from arts and science colleges of Kottayam district selected through two stage random sampling. Data were collected from the students using a self-administered questionnaire consisting of socio-demographic questionnaire, the satisfaction with life scale and the Multidimensional Scale of Perceived Social Support (MSPSS). Data analysis was done using SPSS version 25. Results: Among the 464 study participants, majority (74.1%) were having high social support. 51(11%) students were found to be extremely satisfied with life and 96 (20.7%) satisfied with life. The life satisfaction scores among female study participants was found to be statistically significantly higher than males (Z=2.433, p=0.015). Life satisfaction had a statistically significant positive correlation with total perceived social support (Spearman’s rho=0.391, p<0.001) and perceived support from family (Spearman’s rho=0.394, p<0.001), friends (Spearman’s rho=0.187, p<0.001) and significant others (Spearman’s rho=0.280, p<0.001). Conclusions: Regular assessment of social support and life satisfaction of college students should be done. Steps should be taken ensure adequate social support to college students.